Peran Iklim Sekolah terhadap Perilaku Cyberbullying - Waji, Ria Sakinah; Linggi, Alexander Indrakusuma (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The use of digital technology can result in cyberbullying behavior. Cyberbullying behavior is a cruel behavior that disturbs other individuals that is done consciously and repeatedly using technology media. Adolescents as students will spend more time at school. One of the researcher's assumptions is that the influence of the role of school climate has a role in the occurrence of cyberbullying behavior. "Invisible" bullying is very possible to occur in schools but is not seen by the school. The research method uses a quantitative approach with a correlational research type. Respondents in the study are 127 early adolescents with an age range of 13-16 years. The results of the study showed a significant relationship between school climate and cyberbullying behavior in adolescents (p = 0.013). The correlation coefficient of -0.220 indicates a weak negative relationship, where a better school climate tends to reduce the level of cyberbullying, although there are other influencing factors.